CORPORATE IMAGE: ELEMENTS NECESSARY TO CONSOLIDATE ORGANIZATIONS IN THE MARKET. CASE: CONSTRUCTION COMPANIES. - Alcalá, María Cristina
The purpose of this research is to analyze the elements of corporate image to become important in the market of construction companies, in scenarios of market globalization also doctrinally sustain the reason why some companies should consolidate its image as part of a positioning strategy and consolidation in time with its stakeholders. We worked with authors like Pizzolante (2006), Pizzolante (2006) Capriotti (2006), Van Riel (2007). The research used was non-experimental descriptive and cross-sectional design. The sample consisted of 48 construction companies belonging to the Venezuelan construction chamber, Zulia region. The results allowed us to know which are handled at a moderate level, with weaknesses in terms of corporate identity and corporate culture, as well as perception, reputation and corporate communication, even if it must be enclosed that prestige comes with strength in these construction companies.